1994
DOI: 10.1159/000276632
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Receptors in Papilloma, Normal Mucosa and Polyps of the Nose

Abstract: Sex steroid hormone receptors (SSHR) were determined in 14 cases of sinonasal papillomas, 17 cases of nasal polyps and in the normal nasal mucosa of 13 patients. The determination of SSHR was done by the dextran-coated charcoal assay from cytosol protein. All the cases of sinonasal papilloma were SSHR negative, while some specimens of normal nasal mucosa contained small amounts of SSHR. In addition, some cases of nasal polyps were found to contain low concentrations of the receptors, but concentrations were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This is particularly about estrogen through the exertion of anti-inflammatory and pro-inflammatory effects at different physiological levels [26, 27]. On the other hand, the dynamics of SANC is indirectly affected by the existence of sex steroid receptors in the anterior nares, in addition to the microenvironment of nasal cavity which is influenced by sex hormones [24, 28]. The peak competition of respiratory pathogens to colonize in the anterior nares is in the first years of life, by which interfering of the bacteria confers their elimination or establishment [1].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly about estrogen through the exertion of anti-inflammatory and pro-inflammatory effects at different physiological levels [26, 27]. On the other hand, the dynamics of SANC is indirectly affected by the existence of sex steroid receptors in the anterior nares, in addition to the microenvironment of nasal cavity which is influenced by sex hormones [24, 28]. The peak competition of respiratory pathogens to colonize in the anterior nares is in the first years of life, by which interfering of the bacteria confers their elimination or establishment [1].…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] Early animal models, however, showed some consistency in findings that estrogen at the high-range level could predispose the host animals to bacterial colonization [ 47 ] or infection. [ 48 , 49 ] With later studies revealing that sex steroid receptors also existed in the nasal cavity [ 50 ] and that menstrual cycle affected allergic reactions of the nose [ 51 , 52 ] and the skin, [ 53 ] Winkler et al were among the first to use the karyopyknotic index (to represent women's estrogen level) and compared nasal carriage rates in both premenopausal and postmenopausal women. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…The significantly higher incidence in males suggests possible sexual hormone dependence. Only two studies in 1994 and 1998 studied the expression of sex hormones receptors on limited number of case histories are reported in the literature [1819]. The analysis of these studies showed the absence of PGR-ER receptor expression or weakly positive for PR.…”
Section: Discussionmentioning
confidence: 99%